Evaluasi Kinerja Campuran AC-WC dengan Substitusi Parsial Aspal Minyak oleh Asbuton B520 Kadar Rendah - Adinda Putri; Hakzah Hakzah; Imam Fadly (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The growth of road infrastructure in Indonesia encourages the use of more efficient and sustainable pavement materials. This study aims to evaluate the effect of partial substitution of asphalt with low-grade Asbuton B5/20 (2–4%) on the mechanical performance of AC-WC mixtures. Testing was conducted using the Marshall method with parameters of stability, flow, Marshall Quotient (MQ), VIM, VMA, and VFB, and referring to the General Specifications of Bina Marga 2018 Revision 2. The results show that the addition of 2% Asbuton yields optimal performance with an MQ value of 366.18 kg/mm and all volumetric parameters meeting the specifications. An addition above 2% causes a decrease in stability and stiffness, although it's still within standard limits. These findings indicate that Asbuton B5/20 can be used as a partial substitute for asphalt binder at an optimum content of 2%, supporting the efficiency of local materials for tropical road pavements. Further studies are recommended to test the field performance and long-term durability of the mixture.